The Role of Islamic Banking in Improving Financial Literacy in Kindergarten Malaysia - Aurora, Katherine Helen; Amalia, Alfi (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2024)
This study aims to examine the role of Islamic banking in enhancing financial literacy among Malaysian preschoolers. The qualitative method was employed, with data collection conducted through direct observations. Findings revealed the significant contribution of Islamic banking to improving financial literacy among young children. Through educational and training programs organized by students in Islamic banking programs, children are introduced to fundamental financial concepts such as savings, expenditure, and investment tailored to their level of comprehension. This research contributes to understanding the importance of early financial education in nurturing financial literacy skills among children.